Aktivitas Enzim dan Identifikasi Fenotipik Isolat Kapang Aspergillus Kelompok Flavi Dari DUCC (Diponegoro University Culture Collections) - Karima, Radhita; Rukmi, MG Isworo; Kusumaningrum, Hermin Pancasakti (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Fungi has an important role as decomposer since they can produce hydrolytic enzymes. The enzyme produced by fungi can be useful for industrial and biotechnology purposes. Aspergillus section Flavi are known to have the ability in producing several enzymes. The aims of this study were to find out the ability of Aspergillus section Flavi from Diponegoro University Culture Collection in producing amylase, protease and cellulase enzymes and also identify the species using phenotypic method. The fungal enzymatic activity was examined by calculating enzymatic index on specific media. The results showed that all isolates have a potential as enzyme producers. Phenotypic identification were characterized based on macro- and micromorphology. Isolates F130, F80CB, F138 dan F10A were identified as A.tamarii, while F43 and F20A were identified as A.flavus.